Shear Strengthening of Reinforced Concrete Beam Using Wire Mesh–Epoxy Composite - Mustafa Al-Bazoon; Abdulkhaliq Jaafer; Haidar Haidar; Abbas Dawood (Salehan Institute of Higher Education, 2022)
This experimental research aims to study the use of wire mesh–epoxy composite (WMEC) as a shear-strengthening technique for reinforced concrete (RC) beams by focusing on the following parameters: (1) presence of shear reinforcement in the shear span; (2) type of strengthening technique (U-jacketing, vertical U strip, or inclined strip); and (3) number of wire mesh layers (three or six layers). Nine simply supported rectangular RC beams were tested under two monotonic point loads. The testing specimens were divided into two groups: (1) five beams without shear reinforcement and (2) four beams with shear reinforcement. Load–deflection relationship, shear ductility index, beams’ stiffness, energy absorption, crack propagation, mode of failure, and strain were studied for all testing specimens and compared with those of the control beams to measure the improvement from WMEC addition. Results showed that all WMEC types enhanced the shear capacity. Among the three shear-strengthening types, the continuous U-jacket scheme had a higher effect, increasing the shear capacity between 33.4 and 95.9% and the shear ductility index by 23% relative to those of the reference specimens. The shear capacity improvement by WMEC for the beams without shear steel reinforcement was greater than that for the beams with shear reinforcement under the same shear-strengthening configuration. When the number of wire mesh layers was doubled, the ultimate load was further increased from 33.4 to 57.8%. This research showed that WMEC is a practical and excellent shear-strengthening technique for RC beams. Doi: 10.28991/CEJ-2022-08-06-09 Full Text: PDF